2021
DOI: 10.3174/ajnr.a7072
|View full text |Cite
|
Sign up to set email alerts
|

Brain and Lung Imaging Correlation in Patients with COVID-19: Could the Severity of Lung Disease Reflect the Prevalence of Acute Abnormalities on Neuroimaging? A Global Multicenter Observational Study

Abstract: PURPOSE: Our aim was to study the association between abnormal findings on chest and brain imaging in patients with coronavirus disease 2019 (COVID-19) and neurologic symptoms. MATERIALS AND METHODS: In this retrospective, international multicenter study, we reviewed the electronic medical records and imaging of hospitalized patients with COVID-19 from March 3, 2020, to June 25, 2020. Our inclusion criteria were patients diagnosed with Severe Acute Respiratory Syndrome coronavirus 2 (SARS-CoV-2) infection with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 26 publications
0
31
2
Order By: Relevance
“…Although COVID-19 is seen as a disease that primarily affects the lungs, it may also damage other organs, including heart 93 , 99 and brain, 93 , 99 102 and many long-term COVID-19 effects are still unknown. The COVID-19 patients have to be closely monitored even after their recovery, when imaging and AI may play a pivotal role.…”
Section: Ai Using Clinical Histopathology and Genomics With Imaging Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Although COVID-19 is seen as a disease that primarily affects the lungs, it may also damage other organs, including heart 93 , 99 and brain, 93 , 99 102 and many long-term COVID-19 effects are still unknown. The COVID-19 patients have to be closely monitored even after their recovery, when imaging and AI may play a pivotal role.…”
Section: Ai Using Clinical Histopathology and Genomics With Imaging Datamentioning
confidence: 99%
“…96 The imaging characteristics can be used for prognosis assessment 97 and evaluation of the extent of disease, 11 and it has potential to predict the length of hospital stay. 98 Although COVID-19 is seen as a disease that primarily affects the lungs, it may also damage other organs, including heart 93,99 and brain, 93,[99][100][101][102] and many long-term COVID-19 effects are still unknown. The COVID-19 patients have to be closely monitored even after their recovery, when imaging and AI may play a pivotal role.…”
Section: Covid-19 Severity Assessment/prognosismentioning
confidence: 99%
“…Studies have shown that patients with COVID-19 with acute neuroimaging abnormalities are more likely to have an ischemic stroke. Neuroimaging features of these patients are not invariable but are predominated by acute ischemic infarction, intracranial hemorrhage, and leukoencephalopathy [ 81 ]. COVID-19 is an independent risk factor for acute ischemic stroke and a valid indicator of poor prognosis.…”
Section: Examination Methods Reflecting Nervous System Damage In Covid-19 Patientsmentioning
confidence: 99%
“…Ultimately, this cascade could result in neuronal and astroglial injury/death that will present as cognitive decline [208]. As worsening pulmonary health is correlated with neurological symptoms in COVID-19 patients, the hypoxia cascade is a plausible component of detrimental neurological alterations [210]. Fibrosis is a possible long-term pulmonary consequence from COVID-19, especially after long-duration severe disease, which can reduce overall lung capacity and reduce the efficiency of gas exchange [211].…”
Section: Pulmonary Renal and Liver Interactions With Covid-19mentioning
confidence: 99%